Transcriptomics combined with metabolomics unveiled the key genes and metabolites of mycelium growth in Morchella importuna - Fan, Tingting; Ren, Rui; Tang, Shaojun; Zhou, Yiyun; Cai, Meng; Zhao, Wenwen; He, Yuelin; Xu, Jun (Frontiers in Microbiology, 2023)
Morels (Morchella) are one of the most popular edible fungi in the world for their rich nutrition and delicious taste. Earlier research indicates that the production of fruiting bodies can be effected by the growth of mycelium. To investigate the molecular mechanisms underlying mycelium growth in Morchella importuna, we performed transcriptome analysis and metabolomics analysis in three growth stages of hypha of M. importuna. As a result, 24 differentially expressed genes, such as transketolase (tktA), glucose-6-phophate dehydrogenase (G6PDH), fructose-diphosphate aldolase (Fba), ribose-5-phosphate isomerase (rpiA), and 15 differentially accumulated metabolites including succinate, oxaloacetate and so on, were identified and considered as the key genes and metabolites to mycelium growth in M. importuna. In addition, the Guanosine 3',5'-Cyclic Monophosphate (cGMP) and Guanosine-5'-monophosphate (GMP) and several small peptides were found to differentially accumulated in different growth stages. Furthermore, five pathways including Starch and sucrose metabolism, Pentose and glucuronate interconversions, Fructose and mannose metabolism, Tyrosine metabolism and Purine nucleotides enriched by most DEGs existed in three compared groups were also recognized as important pathways for development of mycelium in morels. The comprehensive transcriptomics and metabolomics data generated in our study provided valuable information for understanding the mycelium growth of M. importuna, and these data also unveils the key genes, metabolites and pathways involved in the mycelium growth. This research provides great theoretical basis for stable production and breeding of morels